The Effect Of Secondary Reserve On The Reliability Of Bank Jatim - AN Rahmatika, Arivatu Ni'mati Rahmatika; Anggraeni, Trisna Putri Anggraeni (LPPM-ITEBA, 2025)
This study aims to analyze the effect of secondary reserves on the reliability of Bank Jatim. The secondary reserve in this study consists of demand deposits, placements in other banks, and securities, while bank reliability is measured based on total liabilities. The data used is secondary data from Bank Jatim's financial statements. The research method employed is multiple linear regression using IBM SPSS Statistics 25. The results show that the variable loans and sharia payments (X4) significantly affects the reliability of Bank Jatim, with a significance value of 0.029 (<0.05). Meanwhile, the variables demand deposits (X1), placements in other banks (X2), and securities (X3) do not significantly influence bank reliability. The coefficient of determination (R²) of 0.229 indicates that 22.9% of the variation in Bank Jatim's reliability can be explained by secondary reserves, while the remaining percentage is influenced by other factors outside the research model.